On the cross-city growth drivers of the most vulnerable region of Brazil. - Martins, Hercilane Gomes (2022)
We address the heterogeneous and worrying growth path of 925 cities located in the Northeast region of Brazil. This region has about 57 million inhabitants and has historically had the lowest socio - economic indicators in Brazil. We propose an innovative specification of the neoclassical growth model, by including additional and idiosyncratic sources of cross - city variation. We use growth drivers on human capital, financial system, business environment and social infrastructure. Considering 6452 observations for the period from 2009 to 2015, our main findings, suggest a robust and significant role played by the levels of education of formal workers (elementary, high school and higher education), rural financing (agricultural and livestock), real estate financing and FIRJAN indices (health, and employment). For cities with higher GDP per capita, water supply also seems to be relevant. In terms of convergence, Brazilian states seem to converge at a faster rate than cities in the Northeast. We expanded our investigation to the nine states of northeastern Brazil and despite finding results with low convergence and little significance in the variables studied, we were able to show the need for a closer look on the part of public policy makers on the most needy cities. These unprecedented conclusions are useful in the focused and strategic conduct of efficient and effective public policies.